ANALISIS PENGGUNAAN LAPORAN ARUS KAS DALAM MENILAI KINERJA PT. MAGENTA JAYA LESTARI DI BANDAR LAMPUNG - Rina Milyati Yuniastuti (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2010)
Cash flow statement is useful for managers internally and externally to investors andcreditors in making business decisions because of the cash flow statement provides importantinformation from the perspective of cash basis (cash basis) that complements the income statementand balance sheet so that it can describe more fully on business activities and financial position.Based on quantitative analysis is known that in the year 2008 according to the calculation ofthe ratio of cash flow to net income to increase operating cash flow performance than indicated onlyby net income alone Based on qualitative analysis is known that the management of cash from theyear 2007 - 2009 have not been managed properly assessed because of cash from operations isvery small value is not comparable with the level of sales and a huge decline in 2009.